2 Agri-wastes for biocomposites - Leao, Alcides Lopes [UNESP]; Cesarino, Ivana [UNESP]; Fernandes, Luis Guilherme [UNESP]; Santos, Gloria [UNESP]; Jawaid, Mohammad (Elsevier, 2025)
The growing demand for agricultural production worldwide for food and biofuel has generated large amounts of residues called agricultural wastes or agri-wastes (AWs). The basic composition of AWs is cellulose, lignin, hemicelluloses plus minor components such as oil, extractives, etc. Therefore, they can also be called lignocellulosic materials. Nowadays, with the importance of the circular economy, more emphasis has been placed on strategies such as biomass valorization and the biomass cascade approach, which aim to create added-value products. The AWs are generated from different sources in the field, including crop residues, livestock, and aquaculture, but also in the processing industries for food or biofuel conversion. Among the billion tons generated annually, most are burned or used for composting or simply buried in the soil. AWs and their processing are a global issue since the vast majority are not utilized in optimized ways. Although some new strategies can bring more technological tools to this area, such as green hydrogen, the main topic of the present chapter is the review of the current applications of AWs, including biopolymers, bioenergy, and chemical feedstock. The adding value strategy and the biomass cascade approach can result in very competitive materials compared to their fossil-based counterparts.